2011
DOI: 10.1016/j.whi.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sexual Orientations and Their Experiences of Sexual Assault Before and During University

Abstract: Bisexual and lesbian women are more likely than heterosexual women to be sexually assaulted before and during university. Sexual assault before university is linked to sexual assault during university for all women, with this association being especially pronounced among non-heterosexuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 32 publications
7
75
1
2
Order By: Relevance
“…We mitigated potential confounding by controlling for demographic variables empirically associated with sexual assault victimization and theoretically associated with campus climate (ACHA, 2012, 2013, 2014; Blosnich & Bossarte, 2012; Blosnich & Horn, 2011; Cantor et al, 2015; Coulter et al, 2015; Coulter et al, 2017; Krebs et al, 2016; Martin et al, 2011; Sinozich & Langton, 2014). Sexual identity was operationalized via the following question: “Which term best describes your sexual identity?” Response options included asexual, bisexual, gay, genderqueer, heterosexual, lesbian, man loving man, pansexual, queer, questioning, woman loving woman, and other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We mitigated potential confounding by controlling for demographic variables empirically associated with sexual assault victimization and theoretically associated with campus climate (ACHA, 2012, 2013, 2014; Blosnich & Bossarte, 2012; Blosnich & Horn, 2011; Cantor et al, 2015; Coulter et al, 2015; Coulter et al, 2017; Krebs et al, 2016; Martin et al, 2011; Sinozich & Langton, 2014). Sexual identity was operationalized via the following question: “Which term best describes your sexual identity?” Response options included asexual, bisexual, gay, genderqueer, heterosexual, lesbian, man loving man, pansexual, queer, questioning, woman loving woman, and other.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cisgender (i.e., nontransgender) women have long been known to be at significantly greater risk of sexual assault than cisgender men (ACHA, 2012, 2013, 2014; Cantor et al, 2015; Krebs et al, 2016; Sinozich & Langton, 2014). Emerging research shows that, compared with cisgender undergraduate students, sexual assault is significantly more prevalent among transgender students (Cantor et al, 2015; Coulter et al, 2015; Coulter et al 2017; Krebs et al, 2016), and compared with heterosexuals, sexual assault is significantly higher among gay/lesbian and bisexual undergraduates (Blosnich & Bossarte, 2012; Blosnich & Horn, 2011; Coulter et al, 2017; Krebs et al, 2016; Martin, Fisher, Warner, Krebs, & Lindquist, 2011). With sexual- and gender-minority students (e.g., lesbian, gay, bisexual, and transgender [LGBT] people) comprising a substantial size of the undergraduate population (estimates range from 9.9% to 19.9% for sexual-minority populations, and 0.2% to 1.8% for gender-minority populations; ACHA, 2012, 2016b; Cantor et al, 2015), sexual assault among these populations is a substantial public health concern worthy of further research.…”
Section: Introductionmentioning
confidence: 99%
“…Cisgender (i.e., not transgender) women are at heightened risk for sexual assault compared to cisgender men (American College Health Association, 2012, 2013, 2014; Cantor et al, 2015; Krebs et al, 2016; Sinozich & Langton, 2014). Transgender people are at higher risk for sexual assault than their cisgender counterparts (Cantor et al, 2015; Coulter et al, 2015; Krebs et al, 2016), and gay/lesbian and bisexual people are at greater risk of sexual assault than heterosexuals (Blosnich & Bossarte, 2012; Blosnich & Horn, 2011; Krebs et al, 2016; Martin, Fisher, Warner, Krebs, & Lindquist, 2011a). Meanwhile, racial/ethnic differences in sexual assault among college students are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Cantor et al's (2015) college campus survey includes questions about gender identity, including nonbinary gender, and offers valuable insight into the campus experience of those students who experience the highest levels of sexual assault and misconduct: female and transgender, genderqueer, non-conforming, and questioning students (p. iv). Further, Martin et al (2011) found higher rates of sexual assault before and during college among bisexual and lesbian women as compared to their heterosexual counterparts.…”
Section: Marginalized Identities and Sexual And Gender-based Violencementioning
confidence: 89%
“…Specific to college and general populations, there is research that aims to examine the complexity of the relationship between the continuum of sexual and gender based violence and gender and/or sexual minorities (Masawa, 2009;Meyer, 2008;Nagoshi et al, 2008;Aosved & Long, 2006;Martin et al, 2011). Masawa (2009) found that higher levels of conservative values and hostile sexism was correlated across sex with both homophobia and transphobia; among female participants, higher levels of belief in traditional gender roles and RMA correlated with higher levels of transphobia; and, among male participants greater aggression proneness was associated with higher levels of transphobia.…”
Section: Marginalized Identities and Sexual And Gender-based Violencementioning
confidence: 99%